Detector developments for photon science at DESY - Graafsma, Heinz; Correa, Jonathan; Fridman, Sergei; Hirsemann, Helmut; Hosseini-Saber, S. M. A.; Ignatenko, Alexandr; Klujev, Alexander; Lange, Sabine; Laurus, Torsten; Marras, Alessandro; Pennicard, David; Rah, Seungyu; et al. (Frontiers in Physics, 2024)
The past, current and planned future developments of X-ray imagers in the Photon-Science Detector Group at DESY -Hamburg is presented. the X-ray imagers are custom developed and tailored to the different X-ray sources in Hamburg, including the storage ring PETRA III / IV; the VUV-soft X-ray free electron laser FLASH, and the European Free-Electron Laser. Each source puts different requirements on the X-ray detectors, which is described in detail, together with the technical solutions implemented.